Christian Persecution in Antiquity - Kinzig, Wolfram (Baylor University Press, 2021)
Cover Page -- Map of the Roman Empire and Its Provinces in the Fourth Century -- Half Title Page, Title Page, Copyright -- Contents -- Preface to the English Edition -- Introduction: The Cruelty and Fascination of Ancient Persecutions of Christians -- 1. The Marginalization of Christianity within Judaism -- 2. Christianity's Offensiveness: Ideological Parameters of the Ancient Conflicts -- 3. Legal Procedures and Punishments -- 4. Persecutions in Rome under Nero and Domitian -- 5. Christians as Victims of Local Police Actions (111-249) -- 6. A Decade of Persecution: From Decius to Valerian (249-260) -- 7. The Fiercest Attack on Ancient Christianity: The 'Great Persecution' under Diocletian and Its Aftermath -- 8. Later Repressions of Christians in the Roman Empire -- 9. Late Antique Persecutions outside the Roman Empire -- 10. The Dispute about Repentance after Apostasy -- Concluding Observations -- Notes -- Further Reading -- Timeline of the Persecution under Diocletian -- Index of Names.